'... but you shall let every girl live' : reading Exodus 1:1-2:10 the Bosadi (Womanhood) way - Masenya, Madipoane (Old Testament essays, 2002)
Biblical texts read at face value and outside their contexts, may give an impression of what they do not say. Words and phrases acquire different meanings depending on who says them and in what circumstances they are being said. The present text seeks to investigate what the phrase '... you shall let all girls live' (Ex 1:22) could mean when read from the perspective of African-South African women's experiences. Does the text imply that the bodies which must survive (female bodies) versus those which must suffer death (male bodies) are as valued and as safe as is apparently the case? Are these words, which appear to have the females' interest at heart (about persons marginalised on the basis of their ethnicity, age and gender), uttered by the powerful other, as empowering as they appear to be? If a hermeneutics of Bosadi is applied to Exodus1:8-2:10, how helpful may the reading of this pericope be towards the building of respect for female bodies? These questions seek to unmask differing ideologies surfacing in Biblical texts, an exercise which will hopefully lead to a better appreciation of what Biblical texts can mean to readers in different contexts.